2003
DOI: 10.1212/01.wnl.0000070183.30517.2f
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of the acute and chronic effects of cooling therapy for MS

Abstract: Cooling therapy was associated with objectively measurable but modest improvements in motor and visual function as well as persistent subjective benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…More promising may be exploration of an inflammatory etiology for MS fatigue, which is supported by a link between fatigue and inflammatory markers (tumor necrosis factor-alpha and interferon-gamma) 18 , and by the link between fatigue and elevated body temperature presented herein. Consistent with our observation linking MS fatigue and elevated body temperature, RCTs of cooling garments 1920 and antipyretic medication (aspirin) 21 have been effective in treating MS fatigue. Our findings linking warmer body temperature and MS fatigue help explain the efficacy of cooling/antipyretic treatments, and encourage further research on such treatments for MS fatigue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More promising may be exploration of an inflammatory etiology for MS fatigue, which is supported by a link between fatigue and inflammatory markers (tumor necrosis factor-alpha and interferon-gamma) 18 , and by the link between fatigue and elevated body temperature presented herein. Consistent with our observation linking MS fatigue and elevated body temperature, RCTs of cooling garments 1920 and antipyretic medication (aspirin) 21 have been effective in treating MS fatigue. Our findings linking warmer body temperature and MS fatigue help explain the efficacy of cooling/antipyretic treatments, and encourage further research on such treatments for MS fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…To date, fatigue in MS patients has been notoriously difficult to treat, and many patients are still prescribed stimulants (modafinal) despite several failed RCTs. 1416 In contrast, RCTs of cooling garments 1920 and antipyretics (aspirin) 21 have effectively reduced fatigue in MS patients. Our observation of elevated body temperature linked to worse fatigue in RRMS patients helps explain the effectiveness of previous cooling/antipyretic treatments, and encourages further research on cooling/antipyretic treatments of fatigue in RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…Transient cooling of the body or of arms and legs using cold packs, cold baths or air-conditioning may improve postural stability and muscle strength of the legs (class II evidence [38]), gait (class III evidence [39]) and also fatigue (class III evidence [40]). Cooling garments may result in a better Multiple Sclerosis Functional Composite (MSFC, class II evidence [41]). It can result in a distinct reduction of fatigue and may last from 30–45 min up to several hours.…”
Section: Fatiguementioning
confidence: 99%
“…Thus, different studies have attempted to control patients' body temperature through body cooling using either cool water [6], or cryotherapy [7,8]. One study reported a significant decrease of 0.3-0.7°C in the body temperature of patients with MS (PwMS) using cooling garments [9].…”
Section: Introductionmentioning
confidence: 99%